2018
DOI: 10.1159/000494047
|View full text |Cite
|
Sign up to set email alerts
|

Intra-Arterial versus Intravenous Contrast and Renal Injury in Chronic Kidney Disease: A Propensity-Matched Analysis

Abstract: Background/Aims: contrast-induced nephropathy (CIN) is well described following an administration of intraarterial contrast, but its occurrence after intravenous (IV) contrast is being questioned. We evaluated the incidence of acute kidney injury (AKI), post-contrast AKI (PC-AKI), CIN, dialysis and mortality in patients with chronic kidney disease (CKD) undergoing non-contrast computed tomography (NCCT) or contrast CT (CCT) or coronary angiography (CoA). Methods: We identified individuals who had CoA or CCT or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…In our aforementioned study, 19 cases adjudicated to be CI-AKI carried no mortality risk, with an overall survival rate similar to that in patients who did not have acute kidney injury. Adjudication is key.…”
Section: Future Directionsmentioning
confidence: 62%
See 1 more Smart Citation
“…In our aforementioned study, 19 cases adjudicated to be CI-AKI carried no mortality risk, with an overall survival rate similar to that in patients who did not have acute kidney injury. Adjudication is key.…”
Section: Future Directionsmentioning
confidence: 62%
“…A recent meta-analysis with more than 1,500 patients undergoing peripheral angiography found a higher incidence of acute kidney injury with iodinated contrast media than with carbon dioxide contrast (11% vs 4%, respectively. 18 In addition, our group recently published a propensity-matched study evaluating rates of acute kidney injury in patients with stage 3 or 4 chronic kidney disease undergoing coronary angiography, contrast-enhanced CT, or nonenhanced CT. 19 Postcontrast acute kidney injury was noted in 27%, 24%, and 24% of patients, respectively. All cases of acute kidney injury were then adjudicated by 2 nephrologists through chart review to ascertain the cause.…”
Section: Mehdi and Colleaguesmentioning
confidence: 95%
“…Two studies focused on critically ill [28,29] and two on pediatric patients [30,31]. Four studies consisted of patients admitted via emergency department [32][33][34][35]; one study examined nephrotic syndrome patients [36]; two focused on patients with chronic kidney disease (CKD) [37,38]; and two on patients hospitalized with AKI [39,40]. Two groups studied septic [38,41] and one cancer patients [42].…”
Section: Resultsmentioning
confidence: 99%
“…These results were echoed in the most recent update of the American College of Radiology consensus statement in which it was declared that the risk of AKI developing following exposure to intravenous iodinated CM has been exaggerated and that the true risk of AKI, related to CM administration, remains uncertain even for patients with severe kidney disease [ 31 ]. It has been suggested that intravenous administration of CM, like with CT angiography, may impose a different risk of AKI than the one associated with arterial administration of CM, like with PCI and TAVI; however, the data is inconclusive [ 32 , 33 , 34 , 35 , 36 , 37 ].…”
Section: Discussionmentioning
confidence: 99%